Comparison of the efficacy and safety of quetiapine and lithium for bipolar depression: A systematic review and meta‐analysis of randomized controlled trials - Masaya Ogasawara; Masahiro Takeshima; Yuichi Esaki; Yoshiyuki Kaneko; Tomohiro Utsumi; Yumi Aoki; Norio Watanabe; Masahiro Suzuki; Yoshikazu Takaesu (Wiley, 2022)
Abstract Aim Pharmacological treatments recommended for bipolar depression are inconsistent across guidelines. We compared the efficacy and safety of antipsychotics and mood stabilizers for bipolar depression. Methods A systemic review and meta‐analysis of randomized controlled trials comparing antipsychotics and mood stabilizers for bipolar depression was conducted based on a literature search of major electronic databases. Results Three studies comparing quetiapine with lithium were identified and analyzed; no other antipsychotic‐mood stabilizer combinations were found. The meta‐analysis revealed no significant differences between quetiapine and lithium for the following outcomes: (1) remission from depressive episodes (risk ratio [RR]: 1.80, 95% CI: 0.51‐6.40, P = 0.36), (2) changes in depressive symptom (standardized mean difference: −0.22, 95% CI: −0.52‐0.08, P = 0.15), (3) changes in social function (standardized mean difference: −0.00, 95% CI: −0.19‐0.18, P = 0.98), (4) suicide‐related events (odds ratio [OR]: 2.35, 95% CI: 0.40‐13.65, P = 0.34), (5) severe adverse events (OR: 1.63, 95% CI: 0.51‐5.20, P = 0.41), (6) dropouts due to adverse events (RR: 1.19, 95% CI: 0.76‐1.87, P = 0.45, 7) dropout for any reasons (RR: 0.95, 95% CI: 0.74‐1.22, P = 0.70). Conclusion Although this study found no differences in the efficacy and safety of quetiapine and lithium for bipolar depression, a comprehensive comparison of antipsychotics and mood stabilizers was not performed. Further studies are needed to clarify which of these, not just quetiapine and lithium, is more useful for bipolar depression.